2020
DOI: 10.1093/jtm/taaa102
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of COVID-19 in pilgrims to Israel

Abstract: This report describes a cluster of SARS-CoV-2 infections in pilgrims returning from Israel to Greece. Out of 53 pilgrims, 48 (90.5%) were tested positive for SARS-CoV-2; of them, 41 (85.4%) developed symptoms consistent with COVID-19, and 7 (14.6%) remained asymptomatic. These cases suggest a high risk of COVID-19 infection for pilgrims traveling during the pandemic. Although at that time the prevalence of the disease was low in the origin and destination countries, crowded exposure to other pilgrims from many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…None of the contact cases who were diagnosed positive for COVID-19 required hospitalization. Further epidemiological investigation revealed that more than 90% of the members of the pilgrim group where tested positive [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…None of the contact cases who were diagnosed positive for COVID-19 required hospitalization. Further epidemiological investigation revealed that more than 90% of the members of the pilgrim group where tested positive [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 27 papers met the criteria for inclusion, reporting on 28 MGE (Figure 1). The MGE and virus epidemiology were extracted from the 27 papers (Table 220- 46). The majority of MGEs were religious in nature (n = 22/28; 78.6%) with one-half of the MGEs studies undertaken in the Kingdom of Saudi Arabia (n = 14/ 28; 50.0%).…”
Section: Resultsmentioning
confidence: 99%
“…The above-mentioned restrictions may have also greatly affected Orthodox pilgrimage, a pivotal aspect of Orthodox spiritual life (Terzidou et al, 2017 ), within and outside Greece. However, evidence about the magnitude of the variations in Orthodox pilgrimages in the era of COVID-19 is still limited (Pavli et al, 2020 ). Hence, one purpose of this review, in addition to analyze the impact of the pandemic on Christian Orthodox religiousness, is to provide some general information about pilgrimage and pious tourism, as being experienced in Greece following the proscriptions to visit Mount Athos, the Shrine of Panagia Evangelistria in Tinos and the Holy Places in Jerusalem.…”
Section: The Burden Of the Pandemic On Devotional Pilgrimagesmentioning
confidence: 99%
“…This was the first month in which traveling in Israel became subject to limitations such as obligatory quarantine upon arrival. At the same time in Greece, on March 3, 2020, two of the first COVID-19 cases were notified to the National Public Health Organization of Greece among pilgrims returning from Jerusalem on February 27, 2020, with a direct flight from Tel Aviv, Israel (Pavli et al, 2020 ). Both pilgrims were symptomatic during the flight.…”
Section: The Burden Of the Pandemic On Devotional Pilgrimagesmentioning
confidence: 99%
See 1 more Smart Citation